CHANGE OF REGULARITIES OF IMMUNE RESPONSE IN WORKERS EXPOSED TO METAL MERCURY VAPORS - G. M. Bodienkova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The clinical-immunological examination of the employees working under conditions of the exposure to the metal mercury vapors has been performed. The change peculiarities of the immune responses have been revealed in the employees in dependence on the development stage of the neurointoxication with the metallic mercury vapors. The correlation between the changes of the individual immunological parameters associated with the dosed mercury load and its contents in the blood and urine has been indicated.